Analysis of Ethical Hearings at the Indonesian Child Protection Commission (KPAI) Without a Code of Ethics - Sitti Hikmawatty; Raden Arif Awangga; Agnestalia Renata; Nurdiansyah (Cognitionis Civitatis et Politicae, 2024)
This article explores and analyzes ethical standards in public institutions, with a primary focus on the Indonesian Child Protection Commission (KPAI). Using a normative legal research approach, the article compares KPAI's ethical standards with other public institutions in Indonesia, as well as with applicable international standards. The results indicate that the absence of an explicit code of ethics in KPAI not only creates legal uncertainty but also weakens the enforcement of disciplinary mechanisms within the institution. Based on an analysis framed by ethical theory and moral philosophy, this article emphasizes the need for comprehensive reforms in KPAI's ethical standards. The recommendations aim to increase accountability, transparency, and public trust in KPAI while strengthening the institution's role in protecting children's rights in Indonesia.